Nonlinear Taxation and International Mobility in General Equilibrium - Eckhard Janeba; Karl Schulz (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the nonlinear taxation of internationally mobile workers in general equilibrium. Contrary to conventional wisdom, in general equilibrium, migration lowers the bottom tax rate but raises the top tax rate, making the optimal tax system more progressive and moving tax rates closer to those in an economy with fixed wages. The intuition is that governments attract high-skilled workers by amplifying pre-tax wage inequality and partly offsetting trickle-down forces from production complementarities. This finding raises doubts about the importance of trickle-down for optimal taxation and offers a novel explanation for why globalization may increase tax progressivity and wage inequality.
Keywords: H21; H24; H73; F22; R13; 330; optimal taxation; general equilibrium; trickle-down effects; migration; tax/subsidy competition